Accuracy of antibiotic concentrations in drug dispensing in neonates: a laboratory-based study - Xin Wang; Wei Zhao; John van den Anker; Guo-Xiang Hao; Yue-E Wu; Li-Yuan Zheng; Wei-Ping Gu; Na Liang; Li-Li Gao; Wen-Wen Guo; Rui-Rui Li (BMJ Publishing Group, 2023)
Background Antibacterial therapy plays a crucial role in neonatal infections. The efficacy of antibacterial agents is closely related to the actual dose given to neonates. So we evaluated factors potentially affecting the actual dose of intravenous antibiotics during dispensing process in neonates.Methods Meropenem, cefoperazone/sulbactam and piperacillin/tazobactam with two strengths were used to evaluate three methods. Method A (MA) was diluted once and the volumes of 5% glucose for MA were meropenem 4.00 mL, cefoperazone/sulbactam 3.00 mL, piperacillin/tazobactam 9.00 mL. Method B (MB) differed by doubling the volume of 5% glucose. The difference in method C (MC) involved diluting with 5% glucose twice. The concentrations were measured by high-performance liquid chromatography. Relative error (RE) was used to evaluate the preparation accuracy.Results The RE values using MA/MB/MC were: (1) meropenem 0.5 g: 15.1%, 8.0%, 10.4%; 0.25 g: 7.8%, 3.1%, 6.0%; (2) cefoperazone/sulbactam 1.5 g: 13.6%, 4.2%, 3.4%; 0.75 g: 8.8%, 3.5%, 4.0%; (3) piperacillin/tazobactam 4.5 g: 18.2%, 8.7%, 6.3%; 562.5 mg: 8.1%, 2.8%, 6.1%. MB was better than MA in all three drugs. No difference in RE values was found between single and double dilution, except meropenem with 0.25 g. Using MB, meropenem and piperacillin/tazobactam with small drug strength had higher accuracy in preparation.Conclusions MB was suitable for neonatal drug dispensing because of its high accuracy and simple operation. Drugs with small strength were promoted due to the high accuracy.